On Medical Professionals and Criminal Liability: A Dark Side of Good Intentions - Стрельцов, Євген Львович; Стрельцов, Є. Л.; Стрельцов, Евгений Львович; Streltsov, Yevhen L.; Streltsov, Yevgen; Streltsov, Yevgen L.; Кузьмін, Едуард Едуардович; Кузьмін, Е. Е.; Кузьмин, Эдуард Эдуардович; Kuzmin, Eduard E. (Warsaw : «Aluna Publishing», 2019)
Introduction: The study is devoted to the complex legal analysis of the crucial issues of criminal liability of medical professionals, including the problem of the definition of the socalled "medical crimes" and liability for such acts. The aim: The objective of the study is to examine unlawful acts of medical professionals, their legal estimation and regulation, ways for improvement. Materials and methods: The study is based on the analysis of scholarly researches, legislation, judicial practice and statistics. Philosophical, general scientific, theoretical and legal methods provided the methodological basis of this research. Conclusions: An attempt is made to identify the essence of the so-called ‘medicalcrimes’ content, alongside with the liability for them. Making reference to overseas experience, the recommendations to improve the criminal legislation are developed.

Вступ: Дослідження присвячене комплексному правовому аналізу найважливіших питань кримінальної відповідальності медичних працівників, у тому числі проблемі визначення так званих «медичних злочинів» та відповідальності за такі діяння. Мета: Мета дослідження – дослідити протиправні дії медичних працівників, їх правову оцінку та регулювання, шляхи вдосконалення. Матеріали та методи: Дослідження базується на аналізі наукових досліджень, законодавства, судової практики та статистики. Методологічну основу дослідження склали філософські, загальнонаукові, теоретико-правові методи. Висновки: Зроблено спробу виявити суть змісту так званих «медичних злочинів», а також відповідальність за них. З посиланням на закордонний досвід розроблено рекомендації щодо вдосконалення кримінального законодавства.
Streltsov Y. L. On Medical Professionals and Criminal Liability: A Dark Side of Good Intentions / Y. L. Streltsov, E. E. Kuzmin // Wiadomosci lekarskie. - T. 72 - Nr. 12 (cz 2). - Warsaw : «Aluna Publishing», 2019. - С. 2573-2578.
Keywords: medical professionals; medical crimes; medical offences; criminal liability; criminal liabilityof medical staff; медичні працівники; медичні злочини; медичні правопорушення; кримінальна відповідальність; кримінальна відповідальність медичного персоналу; Research Subject Categories::LAW/JURISPRUDENCE